Service Quality and Officer Morality in Motor Vehicle Taxpayer Compliance at the Pasangkayu Samsat Office - Masni Masni; Ni Made Suwitri Parwati (DINASTI RESEARCH, 2026)
This study aims to test and analyze the effect of service quality and the morality of officers on the compliance of motor vehicle taxpayers. The population in this study consists of all motor vehicle taxpayers registered at the Pasangkayu Joint Samsat Office, totaling 58,118 taxpayers. Based on the Slovin formula and incidental sampling technique, a sample of 281 was obtained. The data sources used in this study were primary data collected through questionnaires, which were then tested using the SPSS application. The data analysis techniques in this study included validity testing, reliability testing, normality testing, classical assumption testing, as well as multiple regression analysis using SPSS Statistics 27 for Windows. The results of the study show that officers' morality partially affects taxpayer compliance, the quality of service partially does not affect taxpayer compliance, and both the quality of service and officers' morality simultaneously affect taxpayer compliance.